CampusPlay: Leveraging Community-Based Digital Innovation to Boost University Students' Sports Engagement - Ammie Aprilliani; Rachmawati Pertiwi Iriani; Dirrie Nabhila Ginting; Asep Taryana (Al-Qalam Institue, 2026)
This study aims to develop a community-based digital innovation to enhance university students' participation in sports activities. Despite the widespread use of digital technology, students often struggle with limited information, coordination issues, and a lack of collaborative platforms. Using the design thinking approach, the research focuses on the development of the